Studentâs Voices in Reflective Suprasegmental Features Pronunciation Teaching - Suwartono, Suwartono (EDUCARE, 2014)
ABSTRACT: Most of the literature on pronunciation discusses what and how to teach. The learner, that is actually the center of the teaching and learning process, remains little known or untouched. Meanwhile, suprasegmentals are of paramount importance in spoken English. The presence of suprasegmental features in speech contributes heavily to intelligibility. Suprasegmental features cover mainly stress, length, tone, and intonation. These features are essentially the same as prosodic elements of language. Perhaps, to most EFL (English as Foreign Language) learners in Indonesia, these features are complicated to master. Some teachers of English even did not seem to show interest in introducing the features to students. This article highlights the reflective process within the students learning the English pronunciation. The data were collected through diaries. The students were provided with small notebooks to write entries of reaction, perception, and learning experience when they were being taught English suprasegmental features using reflective method. Video was utilized to facilitate student engaging in reflective process through main teaching and learning activities of listening to target model, rehearsing monologue or dialogue, video-recording, and playing video clip. Overall, the majority of reflections revealed that the adoption of video as a reflective tool integrated into communicative language activities has helped the students evaluate and self-monitor their own speech performance in learning the English suprasegmental features pronunciation, which is commonly considered complicated.Â  Â KEY WORDS: Studentsâ voices, reflective, suprasegmental, pronunciation, evaluate, self-monitor, teaching and learning process, diary, and class-room action research.About the Author: Dr. Suwartono is a Senior Lecturer at the Department of English Language Teaching, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Central Java, Indonesia. The author can be reached at: suwartono2006@yahoo.co.idHow to cite this article? Suwartono. (2014). âStudentâs Voices in Reflective Suprasegmental Features Pronunciation Teachingâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.137-144. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 24, 2013); Revised (January 27, 2014); and Published (February 17, 2014).Â  Â